The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/ped.12658
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings in 10 children with H275Y influenza A(H1N1)pdm09 virus infection

Abstract: Fever in the H275Y children treated with oseltamivir and peramivir resolved rapidly during the 2013-2014 influenza season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…The duration of fever among the five cases was 1–3 days, in range with the data reported on patients infected with the H275Y mutant virus during the 2013–2014 season in Hokkaido, Japan [17]. Kakuya et al demonstrated in a small number of pediatric patients that oseltamivir and peramivir retain the clinical effectiveness against the H275Y mutant virus [17]. In contrast, we have previously shown that children less than 6 years of age infected with the seasonal H275Y A(H1N1) virus had delayed fever resolution compared with those infected with the sensitive virus [18].…”
Section: Textsupporting
confidence: 82%
See 1 more Smart Citation
“…The duration of fever among the five cases was 1–3 days, in range with the data reported on patients infected with the H275Y mutant virus during the 2013–2014 season in Hokkaido, Japan [17]. Kakuya et al demonstrated in a small number of pediatric patients that oseltamivir and peramivir retain the clinical effectiveness against the H275Y mutant virus [17]. In contrast, we have previously shown that children less than 6 years of age infected with the seasonal H275Y A(H1N1) virus had delayed fever resolution compared with those infected with the sensitive virus [18].…”
Section: Textsupporting
confidence: 82%
“…All patients started the treatment within 48 h of fever onset and fully recovered without complications. The duration of fever among the five cases was 1–3 days, in range with the data reported on patients infected with the H275Y mutant virus during the 2013–2014 season in Hokkaido, Japan [17]. Kakuya et al demonstrated in a small number of pediatric patients that oseltamivir and peramivir retain the clinical effectiveness against the H275Y mutant virus [17].…”
Section: Textsupporting
confidence: 71%
“…However, there was no difference in the clinical course or duration of intubation and admission, when compared with the five other cases. Resistance to oseltamivir is reportedly not associated with duration of fever in the patients with H1N1pdm09 infection [25]; however, evidence regarding the association with respiratory distress is lacking.…”
Section: Discussionmentioning
confidence: 98%
“…Only one report is available at the moment regarding the efficacy of peramivir treatment against H275Y mutant A(H1N1)pdm09 virus. Kakuya et al demonstrated in a small number of pediatric patients that oseltamivir and peramivir can retain some clinical effectiveness against the H275Y mutant virus, in a community outbreak in Hokkaido, Japan during the 2013–2014 season [94]. To retain the optimal concentration in blood and the upper respiratory tract in these children, two IV peramivir doses per day (5 or 10 mg/kg at every 12 h) are preferable based on the PK/PD dynamic models [90].…”
Section: National Influenza Surveillancementioning
confidence: 99%